Hubungan Polusi Udara Perkotaan dengan Kejadian Prematuritas dan Gangguan Pertumbuha Janin di Indonesia: Scoping Review - Tasya Aida Herfadila; Triana Srisantyorin; Suherman Jaksa (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Urban air pollution is one of the most significant environmental health threats globally. Indonesia, with its high urbanization rate and particulate matter (PM2.5) concentrations nearly eight times above World Health Organization (WHO) guidelines, faces serious challenges related to the impact of air pollution on maternal and fetal health (Soesanti et al., 2023). Exposure to air pollution during pregnancy is associated with various adverse pregnancy outcomes, including low birth weight (LBW), preterm birth, and intrauterine growth restriction (Veras et al., 2022). This scoping review aimed to map and synthesize scientific evidence on the association between urban air pollution and prematurity and fetal growth restriction in Indonesia. A literature search was conducted in three major databases: PubMed (n=245), Scopus (n=238), and Google Scholar (n=248), with a total of 731 articles identified. After duplicate removal and screening, 28 studies were included in the qualitative synthesis, with 15 studies directly relevant to the Indonesian context. Evidence suggests that exposure to PM2.5 and traffic-related pollutants is significantly associated with reduced birth length (-3.83 mm per IQR increase in soot) and an increased risk of preterm birth (OR=2.19) in Southeast Asia, including Indonesia (Thaichana et al., 2025). Underlying mechanisms include oxidative stress, mitochondrial dysfunction, and impaired placental function (Familari et al., 2019).